2016
DOI: 10.1186/s12967-016-1008-4
|View full text |Cite|
|
Sign up to set email alerts
|

Ockham’s razor for the MET-driven invasive growth linking idiopathic pulmonary fibrosis and cancer

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) identifies a specific lung disorder characterized by chronic, progressive fibrosing interstitial pneumonia of unknown etiology, which lacks effective treatment. According to the current pathogenic perspective, the aberrant proliferative events in IPF resemble those occurring during malignant transformation. Main body:Receptor tyrosine kinases (RTK) are known to be key players in cancer onset and progression. It has been demonstrated that RTK expression is sometim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 167 publications
2
16
0
Order By: Relevance
“…Thus, our data strongly suggest that the non-catalytic SEMA domain is involved in neoplastic invasiveness, although no clear mechanistic explanation is given by only biological characterization of SEMA mutants. Notably, we further demonstrated that the occurrence of SEMA mutations is associated with aggressive and radioresistant brain metastasis from known primary (lung) ( Stella et al, 2016a , Stella et al, 2016b ) thus confirming the tumorigenic potential of SEMA-mutated cells. Those findings allowed us to hypothesize that changes affecting the SEMA domain coding sequence may be reflected in structural alteration of the extracellular portion of the MET receptor.…”
Section: The Met-driven Invasive Growth Program In Metastasis and Cupsupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, our data strongly suggest that the non-catalytic SEMA domain is involved in neoplastic invasiveness, although no clear mechanistic explanation is given by only biological characterization of SEMA mutants. Notably, we further demonstrated that the occurrence of SEMA mutations is associated with aggressive and radioresistant brain metastasis from known primary (lung) ( Stella et al, 2016a , Stella et al, 2016b ) thus confirming the tumorigenic potential of SEMA-mutated cells. Those findings allowed us to hypothesize that changes affecting the SEMA domain coding sequence may be reflected in structural alteration of the extracellular portion of the MET receptor.…”
Section: The Met-driven Invasive Growth Program In Metastasis and Cupsupporting
confidence: 70%
“…Notably, MET genetic alteration is being targeted and in some instances quite successfully by various MET inhibitors. Several reports are already available on these topic (for a review see Comoglio et al, 2008 ; Gherardi et al, 2012 ; Stella et al, 2016b ; Ma, 2017 ). Details on anti-MET agents which already landed the clinical arena are summarized in Table 1 .…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…The term is currently most often associated with the field of oncology, where rapid disease progression in cancer results from a series of somatic mutational events, which often clearly define a before- and after-disease state. This dichotomy provides a clear avenue to target treatments to an individual patient’s mutational profile 26 , 27 , 28 , 29 . The term is also used to define the application of genomic profiling and pharmacogenomics in a public health setting 30 , 31 , 32 , 33 .…”
Section: Defining Precision Cardiologymentioning
confidence: 99%
“…In the original version of this article [ 1 ], published on 2 September 2016, the name of author ‘Alice Balderacchi’ was wrongly displayed. In this Erratum the incorrect name and correct name are shown.…”
Section: Erratum To: J Transl Med (2016) 14:256 Doi 101186/s12967-01mentioning
confidence: 99%